Effects of ply angle and blocking on open-hole tensile strength of composite laminates: A design and certification perspective. (15th February 2021) - Chuaqui, T.R.C.; Nielsen, M.W.D.; Colton, J.; Butler, R.; Rhead, A.T.
Abstract: The failure strength of carbon-fibre reinforced plastic laminates under open-hole tension varies considerably with ply angle, ply blocking and loading direction. Here, laminates with various standard-angle and non-standard angle stacking sequences are subjected to both on- and off-axis loading in a comprehensive experimental and progressive damage finite element analysis testing campaign. It is found that interlaminar and intralaminar matrix damage can be beneficial when accumulated sub-critically in ply blocks aligned with loading direction, but can also lead to significant strength decreases owing to edge failure. In such cases, a numerical edge treatment is proposed for more accurate representation of open-hole tensile strength in large structures where holes are positioned away from free edges. The solution suppresses edge failure and results in up to 80% strength increases, challenging the validity of standard open-hole tension testing and current design rules for some applications.